2013
DOI: 10.1136/bmjopen-2013-003573
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of eculizumab for atypical haemolytic uraemic syndrome (aHUS)

Abstract: ObjectiveTo determine the efficacy and safety of eculizumab for patients with atypical haemolytic uraemic syndrome (aHUS), compared with current treatment options.DesignA systematic review was performed according to the general principles of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. All study designs were included, except case histories.ParticipantsAll patients diagnosed with aHUS were included; no age restrictions were used.InterventionsEculizumab compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 51 publications
2
71
0
3
Order By: Relevance
“…Case reports have been published with follow-up ranging from 1 to 3 years from initiation of treatment. 11,14 Respiratory tract infections, hypertension, and gastrointestinal disturbances are the most common adverse events reported, 16 and meningococcal septicemia has been described. 16,17 Administration of eculizumab in immunosuppressed patients may be complicated by meningococcal disease despite previous vaccination, 17 as described in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Case reports have been published with follow-up ranging from 1 to 3 years from initiation of treatment. 11,14 Respiratory tract infections, hypertension, and gastrointestinal disturbances are the most common adverse events reported, 16 and meningococcal septicemia has been described. 16,17 Administration of eculizumab in immunosuppressed patients may be complicated by meningococcal disease despite previous vaccination, 17 as described in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Respiratory tract infections, hypertension, and gastrointestinal disturbances are the most common adverse events reported, 16 and meningococcal septicemia has been described. 16,17 Administration of eculizumab in immunosuppressed patients may be complicated by meningococcal disease despite previous vaccination, 17 as described in our patient. The bactericidal efficiency of the immune response is unknown in patients with complement deficiencies or under complement blockade, and the effectiveness of antibiotic prophylaxis may become problematic with the emergence of resistant strains going forward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NHS England's economic analysis suggests that the discounted incremental cost-effectiveness ratio for eculizumab, versus standard care, is around £521,000 per QALY gained for a 23-year-old cohort. 29 …”
Section: Economics Of Eculizumabmentioning
confidence: 99%
“…Extensive studies showed that hyperactivation of the complement alternative pathway is the main pathogenetic effector mechanism leading to endothelial damage and microvascular thrombosis in most patients with aHUS (1,2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These findings paved the way for complement-tailored treatments (1,11) that have led to impressive improvements in short-and long-term prognosis (12). However, the underlying cause remains elusive for a substantial proportion of patients.…”
Section: Introductionmentioning
confidence: 99%